2016
DOI: 10.1097/01.prs.0000475823.01907.53
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose and Short-Duration Matrix Metalloproteinase 9 Inhibition Does Not Affect Adhesion Formation during Murine Flexor Tendon Healing

Abstract: Background After flexor tendon (FT) injury and repair, adhesion formation is a substantial concern as it can result in loss of motion and functional disability. Mmp9 is a gelatinase that contributes to degradation of extracellular matrix and is expressed during FT healing. Mmp9-/- mice have accelerated remodeling of adhesions during FT healing, relative to wild type mice. The purpose of this study was to investigate whether Ro 32-3555, an Mmp9 inhibitor, can improve FT healing by limiting adhesion formation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This model has been used to assess knock-out mouse models 13,14 , and to test different pharmacological approaches to improve healing 1518 . Histological analyses of this model, using immunohistochemistry and in situ hybridization, can provide important insights in to the localization of key genes and proteins during healing.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been used to assess knock-out mouse models 13,14 , and to test different pharmacological approaches to improve healing 1518 . Histological analyses of this model, using immunohistochemistry and in situ hybridization, can provide important insights in to the localization of key genes and proteins during healing.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, proteome profiling arrays revealed that the release of several angiogenesis‐related proteins was altered in monocyte supernatants after I/R. Especially, MCP‐1, GM‐CSF, MIP‐1α, identified as some of the most enhanced proteins on both profiling arrays, have been described as potent effectors for remodelling and neoangiogenesis by promoting vascular endothelial growth factor‐A (VEGF‐A), endothelial progenitor cell (EPC) migration and recruitment of anti‐inflammatory macrophages (M2) at the site of ischaemic injury, where they participate in tissue recovery …”
Section: Discussionmentioning
confidence: 99%
“…Especially, MCP-1, GM-CSF, MIP-1α, identified as some of the most enhanced proteins on both profiling arrays, have been described as potent effectors for remodelling and neoangiogenesis by promoting vascular endothelial growth factor-A (VEGF-A), endothelial progenitor cell (EPC) migration and recruitment of anti-inflammatory macrophages (M2) at the site of ischaemic injury, where they participate in tissue recovery. [51][52][53] Besides the mentioned proangiogenetic mediators, also a few cytokines with antiangiogenetic potential like Activin A, Angiostatin and Pentraxin-3 was secreted into monocyte supernatants after I/R. The most upregulated antiangiogenic protein found in the culture media was Activin A, a multifunctional cytokine belonging to the TGF-β family.…”
Section: Secretome From Monocytes Subjected To I/r In Vitro Containmentioning
confidence: 99%
“…Many small molecule inhibitors of MMP-9 which effectively treat cancer and arthritis have been studied in human. Figure 1 shows five MMP-9 inhibitors that have reached clinical trials (Batimastat, Marimastat, Prinomastat, Ro32-3555 and CG-S27023A) and another known inhibitor (NFH) which has a crystal structure, complex with the MMP-9 enzyme [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%